Cyto-histological and morpho-physiological responses of common duckweed (Lemna minor L.) to chromium. (February 2016) - Reale, L.; Ferranti, F.; Mantilacci, S.; Corboli, M.; Aversa, S.; Landucci, F.; Baldisserotto, C.; Ferroni, L.; Pancaldi, S.; Venanzoni, R.
Abstract: Along with cadmium, lead, mercury and other heavy metals, chromium is an important environmental pollutant, mainly concentrated in areas of intense anthropogenic pressure. The effect of potassium dichromate on Lemna minor populations was tested using the growth inhibition test. Cyto-histological and physiological analyses were also conducted to aid in understanding the strategies used by plants during exposure to chromium. Treatment with potassium dichromate caused a reduction in growth rate and frond size in all treated plants and especially at the highest concentrations. At these concentrations the photosynthetic pathway was also altered as shown by the decrease of maximum quantum yield of photosystem II and the chlorophyll b content and by the chloroplast ultrastructural modifications. Starch storage was also investigated by microscopic observations. It was the highest at the high concentrations of the pollutant. The data suggested a correlation between starch storage and reduced growth; there was greater inhibition of plant growth than inhibition of photosynthesis, resulting in a surplus of carbohydrates that may be stored as starch. The investigation helps to understand the mechanism related to heavy metal tolerance of Lemna minor and supplies information about the behavior of this species widely used as a biomarker. Highlights: Chromium represents an important environmental pollutant. We investigated the effects of Cr(VI) treatments on Lemna minor plants. Cr(VI) did not interfere with the Chl synthesis but with the energy transfer from antenna to reaction center. A correlation between the starch storage and the reduced growth was also observed. Cr was accumulated only in small quantities in the leaves of Lemna minor .